HEALTH OF CHILDREN - A NEED TO ADJUST NUTRITION? - I.M. Kosenko (Union of pediatricians of Russia, 2010)
Pre-school and school-age children are prone to suffer from malnutrition and are an increased risk group. Using nutritional supplements that contain deficient nutrients is an intelligent solution for children who receive insufficient amount of nutritious substances with food. The author takes a detailed look at the role of rational nutrition. The article illustrates the physiological role of vitamins, minerals, polyunsaturated fatty acids and prebiotics. It details key reasons and consequences of their deficiency in nutrition. It demonstrates the need to prevent deficiency of micronutrients by using vitamin complexes. Key words: children, health, vitamins, minerals, polyunsaturated fatty acids, prebiotics. (Pediatric Pharmacology. 2010; 7(5):60-70)